PENGARUH FRAKSI VOLUME DAN VARIASI PERENDAMAN NaOH TERHADAP KEKUATAN TARIK DAN IMPAK KOMPOSIT BERPENGUAT SERAT AMPAS TEBU - Aden Sanjaya; Juanda Juanda; yuli Dharta (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
This study aims to determine the effect of the duration of immersion of NaOH and the optimal volume fraction of bagasse fiber on tensile strength and impact strength by using Polyester Resin using hand lay-up composite molding method. The object of research is bagasse fiber composites with variations in NaOH immersion and volume fraction. The highest tensile strength in the composite fiber immersion variation for 2 hours with a volume fraction of 15% is 22.3 MPa. Meanwhile, for tilapia the highest impact strength was in the 2-hour fiber immersion variation with 5% bagasse fiber volume fraction of 0.272 J/mm². Meanwhile, the lowest tensile strength is found in the 5% volume fraction, which is 12.8 MPa. And for the lowest strength impact test value in the 15% fraction, which is 0.0113 J/mm².